Pengaruh Model Discovery Learning Berbantuan Media Lingkungan Alam Sekitar terhadap Hasil Belajar IPA - Ni Ketut Intan Bahari; I Wayan Darsana; DB. Kt. Ngr. Semara Putra (Universitas Pendidikan Ganesha, 2018)
The research aims to determining students learning outcome of natural science at class five. In which students are being educated by discovery learning model natural rocks environmental around of students that is learned with conventional leaning program for student class five at elementary school Gugus 5 Blahbatuh. This reseacarching is constitute in experiment researching of Nonequivalent Control Grup Desain. The population 131 students in five grade of elementary school in Gugus 5 Blahbatuh. This sampel was chosenÂ by using randomsampling technique. there two class asresearching sample in which is SD Negeri 4 Pering as experiment group with 32 students and SD Negeri 2 Pering as group control with 30 students, the data collector by using objective test with multiple choice and then analysis, the average of students learning outcomes at natural science for experiment class is 80,00 and at class controlÂ 70,30, the after do to hypothesis examination it gated arithmetic 3,666 in significant 5 % with dk =32+30-2 = 60 prices ttable 2,000 so it can be said arithmetic = 3.666> ttable = 2,000 (a= 0,05, 60 )= 2,000. Then H0 rejected and Ha accepted, this mean the stream of researching that show the indication there are differences in learning outcome at natural science class between experiment class and control class, Therefore we can conclude that used discovery learning model natural aound rock environment media auoud of student learning outcomes for student area effecting of student learning outcomes for students of natural scien at class five in Gugus 5 Blahbatuh in academic years 2016/2017